Independent domination in graphs: A survey and recent results - Goddard, Wayne; Henning, Michael A. (Discrete mathematics, 2013)
A set S of vertices in a graph G is an independent dominating set of G if S is an independent set and every vertex not in S is adjacent to a vertex in S. In this paper, we offer a survey of selected recent results on independent domination in graphs.